2021
DOI: 10.1186/s40170-021-00270-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MYC-enhanced glycolysis for the treatment of small cell lung cancer

Abstract: Introduction The transcription factor MYC is overexpressed in 30% of small cell lung cancer (SCLC) tumors and is known to modulate the balance between two major pathways of metabolism: glycolysis and mitochondrial respiration. This duality of MYC underscores the importance of further investigation into its role in SCLC metabolism and could lead to insights into metabolic targeting approaches. Methods We investigated differences in metabolic pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 61 publications
(99 reference statements)
0
24
0
Order By: Relevance
“…MYC amplification is associated with suppressed immune cell infiltrates and functional pathways ( Wu et al, 2021b ). Although targeting MYC in SCLC has been tested in some preclinical studies ( Cargill et al, 2021 ), there are no defined paths for clinical translation. Furthermore, the effect of immunotherapy in the immunocompetent B6FVBF1/J subcutaneous RPM tumor-bearing model has not yet been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…MYC amplification is associated with suppressed immune cell infiltrates and functional pathways ( Wu et al, 2021b ). Although targeting MYC in SCLC has been tested in some preclinical studies ( Cargill et al, 2021 ), there are no defined paths for clinical translation. Furthermore, the effect of immunotherapy in the immunocompetent B6FVBF1/J subcutaneous RPM tumor-bearing model has not yet been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, proteomic data clearly indicated that the activation of OXPHOS and respiratory chain elements are strongly specific for SCLC-A. It has been recently described that cell lines not expressing MYC (characteristic for SCLC-A 6,8 ) relies more on oxidative metabolism 67 suggesting that SCLC-A tumours might be susceptible to OXPHOS inhibitors. 68 SCLC-N cell lines, which predominantly formed suspension cultures in our study, showed a concordant downregulation of cell adhesion pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to differences in cell death regulation, MYC-high/ASCL1-low SCLC tends to be more proliferative and glycolytic with unique metabolic vulnerabilities ( Mollaoglu et al 2017 ; Huang et al 2018a ; Cargill et al 2021 ). Unbiased metabolite profiling experiments on cell lines and murine tumors have identified key metabolic differences in ASCL1-high versus ASCL1-low SCLC subtypes.…”
Section: Heterogeneity In Therapeutic Responses: Ascl1 Vs Mycmentioning
confidence: 99%